PENDIDIKAN KRISTEN DI ABAD ERA GLOBALISASI: STRATEGIC TEACHING AND LEARNING YANG BERORIENTASI KEPADA STUDENTS-CENTERED - Rufina Leong (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2020)
Abstract: Learning strategies have the purpose of giving awareness to educators to increase their knowledge of technological development skills from the era of globalization. The question that arises: What is Christian Education? What are the effective Christian Education learning strategies? What are the challenges, constraints of implementing Christian Education, and how to overcome them? The answer is: (1) Christian education is a student-centered learning process based on elements of communication, collaborative, critical thinking, creativity, and the application of pure values and ethics. (2) Christian Education learning strategies can be done in accordance with the context of students in the classroom with the following rules: teachers determine the instructor learning process strategy, teachers give time and opportunity, teachers give clear instructions to students, teachers give trust and guidance to students and teachers give students the right to learn. (3) The challenges and constraints of implementing Christian Education and how to overcome it are: First, teachers (lecturers) need to be aware of the importance of diversifying teaching and learning methods to be in line with 21st century education in fulfilling their duties and responsibilities for students . Second, teachers should always be proactive, self-assessing, prepared, confident and take the initiative to strive to improve skills and produce effective teaching techniques that are able to attract students. Abstrak: Strategi pembelajaran mempunyai tujuan memberi kesadaran kepada warga pendidik meningkat pengetahuan keterampilan perkembangan tekonologipada era globalisasi. Persoalan yang timbul: Apa itu Pendidikan Kristen?  Bagaimanakah strategi pembelajaran Pendidikan Kristen yang efektif? Bagaimanakah cabaran, kekangan melaksanakan Pendidikan Kristen,  dan cara mengatasinya? Jawabnya adalah: (1) Pendidikan Kristen merupakn proses pembelajaran yang berpusatkan murid berteraskan elemen komunikasi, kolaboratif, pemikiran kritis, kreativiti, dan aplikasi nilai murni dan etika. (2) Strategi pembelajaran Pendidikan Kristen dapat dilakukan sesuai dengan konteks murid di kelas dengan kaidah-kaidah sebagai berikut: guru menentukan strategi proses belajar pengajar, guru beri masa dan peluang, guru memberikan arahan jelas kepada murid, guru memberi kepercayaan dan bimbingan kepada murid, dan guru memberikan hak murid untuk belajar.  (3) Cabaran dan kekangan melaksanakan Pendidikan Kristen  dan cara mengatasinya adalah: Pertama, guru-guru (pensyarah-pensyarah) perlu sadar akan kepentingan mempelbagaikan kaedah pengajaran dan pembelajaran agar selari dengan pendidikan abad ke-21 dalam menunaikan tugas dan tanggungjawab mereka demi kemenjadian murid. Kedua, guru harus sentiasa bersikap proaktif, menilai diri, bersedia, berkeyakinan dan mengambil inisiatif untuk berusaha meningkatkan kemahiran dan menghasilkan teknik pengajaran berkesan yang mampu menarik minat murid.